THE ELEMENTS OF IDEATIONAL GRAMMATICAL METAPHOR IN READING TEXTS FOR SENIOR HIGH SCHOOL ENGLISH TEXTBOOKS - Diemam Ferzhawana; Siti Aisyah Ginting; Zainuddin Zainuddin (LINGUISTIK TERAPAN, 2019)
This study investigated ideational grammatical metphor in Senior High School English Textbook. The objectives of the study were to identify what ideational grammatical metaphors were used in Senior High School English Textbooks. The research was conducted by applying descriptive qualitative design. The data for this study were texts which were taken from Texts in Senior High School English Textbooks. The data were collected by selecting all the texts in the textbooks, then retyping the passage of the texts, editing the passage by breaking down the clauses into a data, and finally printing out the data. After the data had been collected, they were analyzed by some procedures; identifying the ideational grammatical metaphor in the data, rewording or unpacking the data into a congruent form, making comparisons between the two forms, classifying the classes of ideational grammatical metaphor and its function and analyzing the reason the ideational grammatical metaphor was used in Senior High School English Textbooks. The findings of the study showed that there were four ideational grammatical metaphor used in Senior High School English Textbook, namely the data of epithet = thing, event = thing, event = epithet and head = modifier.Keywords: Ideational Grammatical Metaphor, Senior High School English Textbooks,